AKIBAT HUKUM PEMBATALAN PERJANJIAN BILATERAL TERKAIT PINJAMAN KEPADA CHINA DALAM PERSPEKTIF HUKUM INTERNASIONAL - Tri Murti Lubis (Res Nullius Law Journal, 2021)
The One Belt One Road (OBOR) project initiated by the Chinese Government has gripped countries in the international community. Especially to Southeast Asia, where Malaysia and Indonesia are borrowing countries to China. Replacement of government in Malaysia related to corruption cases 1 MDB, resulting in changes in government policy Malaysia. The cancellation basis, because all the raw materials or the materials used are from China following also engineers and unskilled laborers, thus causing a massive migration from China to Malaysia. In the case of this cancellation, of course, the legal consequences for Malaysia as a borrowing country and China as a lending country. Unlike Indonesia, which until now, it is known that the Indonesian Government has established bilateral relations with the Chinese Government in terms of infrastructure development, such as: toll road and airport in Indonesia. The main problem in this study, namely if this bilateral dispute is brought to the International Court of Justice, is the mechanism for executing an international court decision to be issued later.